(untitled) (Development Service Industry Management, 2024)
The article examines the role of Ukrainian cuisine restaurants in shaping and preserving Ukraine’s cultural identity and analyzes their impact on the development of the restaurant business. The purpose of the study is to determine how national cuisine contributes to strengthening national identity and popularization of Ukrainian culture in modern conditions, and to explore the economic potential of Ukrainian cuisine restaurants in a market environment. The focus is on the fact that Ukrainian cuisine, as an important component of national culture, reflects the historical, ethnographic and regional traditions of Ukraine. Ukrainian restaurants function not only as food outlets but also as cultural venues, popularizing Ukrainian traditions among domestic and foreign consumers. Important traditional dishes, such as borsch, dumplings, and galushky, symbolize national identity and help to shape Ukraine’s positive image on the international stage. The article also highlights the role of restaurants in preserving and reproducing regional culinary traditions that reflect the diversity of cultural practices in all regions of Ukraine. In this context, the article analyzes the activities of individual Ukrainian restaurants that actively integrate elements of cultural heritage, recreate national culinary traditions, and promote the development of the restaurant business through authenticity of dishes and cultural events. In addition, the article focuses on the economic aspects of Ukrainian cuisine restaurants. Their positive impact on the development of the local economy is emphasized, in particular through support for local producers and suppliers, job creation, and stimulation of the tourism industry. Their contribution to the development of gastronomic tourism, which increases the interest of foreign tourists in Ukrainian culture through national cuisine, is also studied. The article notes that Ukrainian restaurants are actively introducing innovations in their operations, using new cooking technologies and modern marketing strategies, which contributes to the growth of the customer base and development of the restaurant business in Ukraine. These establishments are becoming important platforms for popularizing Ukrainian culinary heritage both in the country and abroad, and play an important role in maintaining national identity in the context of globalization. Thus, the article shows that Ukrainian restaurants not only contribute to cultural identification, but also have a significant economic impact on the development of the restaurant business and tourism, making them important participants in the modern market environment.